2016
DOI: 10.1007/978-3-319-47313-0_16
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Voluntary Movement Control and Its Rehabilitation in Cerebral Palsy

Abstract: Cerebral palsy is caused by early damage to the developing brain, as the most common pediatric neurological disorder. Hemiplegia (unilateral spastic cerebral palsy) is the most common subtype, and the resulting impairments, lateralized to one body side, especially affect the upper extremity, limiting daily function. This chapter first describes the pathophysiology and mechanisms underlying impaired upper extremity control of cerebral palsy. It will be shown that the severity of impaired hand function closely r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 105 publications
0
15
0
Order By: Relevance
“…Rather the motor decisions seen in these children are also partly dependent upon how they process and perceive visual information. This view fuels the emerging perspective that the abnormal motor actions seen in children with CP are fundamentally influenced by top-down processing (Gordon, 2016; Kurz et al, 2017a; Lust et al, 2018; Surkar et al, 2018).…”
Section: Discussionmentioning
confidence: 60%
“…Rather the motor decisions seen in these children are also partly dependent upon how they process and perceive visual information. This view fuels the emerging perspective that the abnormal motor actions seen in children with CP are fundamentally influenced by top-down processing (Gordon, 2016; Kurz et al, 2017a; Lust et al, 2018; Surkar et al, 2018).…”
Section: Discussionmentioning
confidence: 60%
“…5,6 The presence of samesided (ipsilateral) CST connections to the affected hand is associated with poorer hand function than preserved crossed CST connections to the affected hand. 2,[7][8][9][10] However, even among children with this ipsilateral CST pattern, there is high variability in hand function. 9 The source of this variability remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Many factors potentially contribute to impaired hand function in children with USCP. The type of corticospinal tract (CST) pattern and the timing, location, and size of brain lesions predict upper-limb function in USCP (see reviews 1,2 ). In many children with USCP, the CST to the affected hand does not originate in the hemisphere contralateral to the affected hand, as it does in typically developing children.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown the benefits of applying CIMT in patients with cerebral palsy to improve the affected limb's function, but it is also significantly efficient when compared to other rehabilitation methods [6,[30][31][32]. The study by Sparrow et al [5] performed with children with brain tumor sequelae, showed beneficial results both qualitatively and quantitatively in the movement of the trained upper limb; in addition, the gains were maintained in the follow-up evaluations for three months.…”
Section: Discussionmentioning
confidence: 99%